2019
DOI: 10.1016/j.jhsa.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Evaluation of Early Postoperative Complications After Distal Biceps Tendon Repairs

Abstract: Purpose The reported incidence of postoperative complications after distal biceps tendon repairs (DBTRs) has been determined largely by retrospective studies. We hypothesized that a large prospective cohort study of DBTRs would demonstrate increased complication rates relative to existing literature values. Secondarily, we hypothesized that most complications would be transient and self-limiting, regardless of the surgical technique employed for the repair.Methods Consecutive patients undergoing acute, primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
(12 reference statements)
1
13
0
1
Order By: Relevance
“…In the study by Matzon et al, 15 the authors found that 2.4% of the operated cases presented complications that required new surgery due to tendon rupture or deep infection. Meanwhile, Samuel E. Ford et al 12 observed a reoperation rate of 4.5%.…”
Section: Discussionmentioning
confidence: 98%
“…In the study by Matzon et al, 15 the authors found that 2.4% of the operated cases presented complications that required new surgery due to tendon rupture or deep infection. Meanwhile, Samuel E. Ford et al 12 observed a reoperation rate of 4.5%.…”
Section: Discussionmentioning
confidence: 98%
“…However, Kodde et al published a 2016 review suggesting fewer complications after a double-incision approach with bone tunnel fixation [ 1 , 6 ]. Lastly, a 2018 prospective study by Matzon et al reported early post-operative complications of 44.6% in a one-incision distal biceps repair cohort compared to 15% in a two-incision repair cohort [ 9 ]. Cumulatively, these findings illustrate that current evidence has yet to reach a consensus on surgical approach and fixation technique to provide optimal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…6,10 Various methods of distal biceps repair have been the subject of extensive research, but currently there is no consensus on the clinical superiority of one approach or fixation method over the other. 1,3,8,[10][11][12]15 Historically, distal biceps repair was performed through an extensile anterior approach which carried a high risk of nerve complications. In the early 1960s, Boyd and Anderson published a two-incision technique to mitigate these risks, but encountered problems with limited forearm rotation due to synostosis related to subperiosteal dissection of the ulna.…”
Section: Level Of Evidence: Level Iv; Economic Analysismentioning
confidence: 99%